Plaque instability biomarkers: a comparison between acute coronary syndrome and chronic stable angina patients - Siew Wai, Fong (2015)

(untitled)
Biomarkers play a pivotal role in the diagnosis and management of patients with acute coronary syndrome (ACS). Some biomarkers, such as C-reactive protein (CRP), soluble CD40 ligand (sCD40L), placental growth factor (PlGF) and myeloperoxidase (MPO) have been reported to be involved in plaque destabilization. The levels of these biomarkers were studied in ACS and chronic stable angina (CSA) patients aged ≤ 45 years and aged > 45 years. The relationship between these biomarkers in the coronary circulation and peripheral circulation was also investigated. This study was the first attempt to investigate the expression of peroxisome proliferator-activated receptors (PPARs) in ACS. A total of 79 patients (ACS: n = 39, CSA: n = 40) was recruited. The blood was sampled from the occluded coronary artery (coronary circulation) and also from the median cubital vein antecubital fossa (peripheral circulation). The serum protein levels of CRP, sCD40L and PlGF and plasma levels of MPO were measured using ELISA. The intracellular levels of PPARs were semiquantified using Western blot. The mRNA levels of the biomarkers were measured by real-time PCR. All ACS patients that underwent six months clinical follow-up was assessed for major adverse cardiac events (MACE) after the acute event. The peripheral levels of CRP, MPO, sCD40L and PlGF were significantly increased in ACS compared to CSA patients. Furthermore, the peripheral concentrations of these biomarkers were significantly correlated with the concentrations found in the coronary circulation. The patients aged below 45 years and above 45 years shared similar profiles of biomarkers. The expression of PPAR-γ was significantly increased in the ACS patients and correlated with both sCD40L and MPO. Serum CRP demonstrated the highest area under the curve value of 0.79 (p < 0.001) in discriminating ACS, followed by PlGF, MPO and sCD40L. In addition, the biomarkers also showed their promising prognostic abilities in predicting 30-day and six-month MACE in ACS patients. In conclusion, this study provided additional information on the proteins and gene expression profiles of plaque instability markers in both CSA and ACS patients. The biomarkers contribute to the formation of unstable plaque by triggering vascular inflammation, firous cap thinning and formation of large lipid core in coronary plaque. Their accuracies in discriminating ACS and predicting MACE also showed promising results.